The Cognitive Achievement of the Physical Management Material and its Relation to the Organizational Deviations of the Training from the Point of View of the Students - Jassem Jaber Mohammed (Journal of Global Pharma Technology, 2018)
The introduction and the importance of research included that the level of sport needs to be built on and the most important of these foundations is the administrative aspect which is the cornerstone of the sport process in all its aspects and this aspect needs an in-depth study that adopts the researcher and the university professor to communicate it to the students and the extent The relationship of the student's cognitive achievement to this information with the organizational deviations of the teacher the problem was formulated in the form of several questions. The most important of which was to remove the organizational deviations of the teacher as a function of predicting the educational achievement of students of the fourth stage of the Faculty of Physical Education and Sports sciences at the University of Babylon Sports management, and there are several objectives, the most notable of which is the prediction of the achievement of the students of the fourth stage of the material of sports management in terms of the organizational deviations of the material teacher from the point of view of the students and the researcher used the descriptive curriculum for the suitability and nature of the study and through the results of the research was Several conclusions, including that the ratio of organizational deviations of the teacher from the point of view of students varies among them where there were several directives and proposals, the most important of which was to rely on the predictive equation produced by this study in other samples.Keywords: Cognitive achievement, Physical management, Material, Training and point of view